MATA PENCARIAN PENDUDUK SUNGAI BATANGHARI SEMBILAN DI PROVINSI SUMATERA SELATAN - Boby Agus Yusmiono; Januardi Januardi (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
The selection of Batanghari Sembilan River as a study because Batanghari Sembilan River is a tributary of the Musi river located in South Sumatra Province. This river is the longest river on the island of Sumatra and the second longest river in Indonesia. This research method is descriptive research that tends to qualitative. Researcher data collection techniques using interviews, observation, and documentation. From the results of the field research, the Batanghari Sembilan community's livelihoods are; 1) Stone or sand, 2) Farmers as irrigated rice fields 3) and green open spaces, 2). Keramba Jaring Apung (KJA) sand mine, 3). Transportation, 4), Fishermen, 5). Side residents looking for gold and Rawas river, 6) timber seekers, 7) plantations 8). Coral finders, 9) coal, 10) Labor and other Keywords: Livelihood, Population, River, Batanghari Sembilan.